THE EFFECT OF CURRENT RATIO, CASH TURNOVER AND INVENTORY TURNOVER ON PROFITABILITY - Mesrawati Mesrawati; Yosemarine Tiosandy; Silvia Silvia; Cindy Cindy; Merlinvia Rezcintami; Tasya Lonika (Universitas Airlangga, 2020)
This study aims to examine and analyze the effect of current ratio, cash turnover, and inventory turnover on profitability in the Food And Beverages subsector listed on the Indonesia Stock Exchange for the period 2012-2017, either partially or simultaneously. The research method used is a quantitative descriptive approach. The population of this study is the Food And Beverages sub-sector companies listed on the Indonesia Stock Exchange in 2012-2017 totaling 19 companies and this sample is 12 companies with purposive sampling technique. This data analysis technique is multiple linear regression analysis. The results showed that partially, current ratio, and inventory turnover have an effect on profitability while cash turnover has no effect on profitability. And simultaneously current ratio, cash turnover, and inventory turnover have an effect on profitability. The coefficient of determination shows 0.656 which means that 65.6% of profitability can be explained by independent variables consisting of current ratios, cash turnover, and inventory turnover and the remaining 34.4% profitability is explained by other variables that are not included in the research model. The conclusion of this study is that only the current ratio and inventory turnover have a significant effect on profitability in the Food And Beverages subsector listed on the IDX for the period 2012-2017.